2008
DOI: 10.1021/ja8018093
|View full text |Cite
|
Sign up to set email alerts
|

Azobenzenes as Light-Controlled Molecular Electronic Switches in Nanoscale Metal−Molecule−Metal Junctions

Abstract: Conductance switching associated with the photoisomerization of azobenzene-based (Azo) molecules was observed in nanoscopic metal-molecule-metal junctions. The junctions were formed by using a conducting atomic force microscope (C-AFM) approach, where a metallic AFM tip was used to electrically contact a gold-supported Azo self-assembled monolayer. The measured 30-fold increase in conductance is consistent with the expected decrease in tunneling barrier length resulting from the conformational change of the Az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
236
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 258 publications
(248 citation statements)
references
References 16 publications
10
236
1
1
Order By: Relevance
“…[3,6]. An additional alternative would be to incorporate switching molecules (for example, azobenzenes [51][52][53], rotaxanes [54,55], and other molecular switches [55][56][57][58]). Such hybrid percolating and molecular systems may allow additional and novel design parameters to be developed, and may well introduce more complex and interesting functionality.…”
Section: Other Memristive Elementsmentioning
confidence: 99%
“…[3,6]. An additional alternative would be to incorporate switching molecules (for example, azobenzenes [51][52][53], rotaxanes [54,55], and other molecular switches [55][56][57][58]). Such hybrid percolating and molecular systems may allow additional and novel design parameters to be developed, and may well introduce more complex and interesting functionality.…”
Section: Other Memristive Elementsmentioning
confidence: 99%
“…The trans-isomer in the low-conducting state transforms into a cis-isomer in the highconducting state, a process that involves short-distance tunnelling transport (h14h2 in Fig. 4b) in cis-aryl azobenzene molecular junctions 23 . The reversible photo-induced conformational changes of the aryl azobenzene monolayer were repeatedly plotted as the change in current density with respect to the switching number (Fig.…”
Section: Molecular Monolayer With Two-terminal Graphene Electrodesmentioning
confidence: 99%
“…It has been shown by conducting atomic force microscopy and Hg drop that the resistance of the molecular junction (i.e., the tunneling barrier) is higher for the trans-AZO SAM (20,21). This is attributed to the decrease in thickness when the SAM switches to the cis form.…”
Section: Figurementioning
confidence: 99%
“…In the last few years, we have extensively investigated the thiol-substituted azo-biphenyl (AZO, Fig. 1A) when chemisorbed on gold surfaces (19)(20)(21)(22). We demonstrated that such a SAM chemisorbed on the planar source and drain electrodes of an OFET can be used to modulate optically the charge injection at the metal-semiconductor interface because of the different tunneling barrier of the cis and trans SAMs (19).…”
mentioning
confidence: 99%